Evacuating Flash Flood Victims: Key Drivers and Psychological Burden - Nivedita Sairam; Doménica Michelle Jaramillo Sánchez; Lisa Dillenardt; Annegret H. Thieken (Journal of Flood Risk Management)
ABSTRACT Effective, timely, and fair evacuation is crucial to mitigate flood impacts. We aim to identify socio‐economic attributes and flood event characteristics influencing evacuation and to quantify the psychological burden of people who experienced evacuation. We implement regression models and matching methods on an empirical dataset (n = 557) collected from the people affected by the 2021 flood in Germany. Homeowners, people with low socioeconomic status, and younger age groups were more likely to be evacuated before/during the flood event. In addition to the severity of the flood experience, high income and insured households were more likely to be evacuated after the event. In instances of evacuation before or during a flood, the psychological burden on those evacuated was found to be 10.3% higher compared to those who were not evacuated. Evacuation did not directly impact the psychological burden of people evacuated after the event. However, the duration of evacuation influenced the psychological burden on the evacuated people. The identification of the drivers of evacuation and quantification of the resulting psychological burden call for improved risk communication, preparedness, and support systems to recognize and address psychological distress in evacuated people.